The influence of E-learning service quality on Gen Z students’ loyalty in Malaysian higher education institutions - Tan, Sarah Woon Xin; Low, Yi En (2024)
The primary goal of this research is to make a clearer connection between students' loyalty and E-learning service quality. The IVs proposed in our research align with the theory with an additional variable. The proposed variable consists of tangible (TAN), reliability (REL), responsiveness (RES), assurance (ASS), empathy (EMP) and switching costs (SC). A total of six hypotheses were developed, to examine whether the E-learning service quality would influence Gen Z students' loyalty in Malaysia HEIs. Likewise, with 384 Gen Z respondents who have experienced online E-learning were collected through the questionnaire distributed. In this research, Statistical Software Package for Social Science (SPSS) software was utilized and analysed on the reliability test, Pearson's Correlation Coefficient Analysis, and Multiple Regression Analysis to illustrate the relationship between IVs and DV. Based on the result of our findings states that all the IVs, except ASS, have a significant relationship with DV. The dimension of SERVQUAL, which is the EMP consists of the largest influence on the students' loyalty in the E-learning context. Finally, this research contributes a better understanding of students' loyalty based on the dimension of SERVQUAL and the additional variable, which is the SC in an E-learning context, to the government, policymakers, owners and service providers of HEIs. Keywords: E-Learning Service Quality, Gen Z, Students’ Loyalty, Malaysia, Higher Education Institutions Subject Area: LB2326.4-2330 Institutions of Higher Education